Waqf Crowdfunding System on Donation Application - Alam, Azhar; Sukmana, Raditya; Priandana, Damara; Bafana, Faiz Adib (Badan Wakaf Indonesia, 2023)
This study aims to design a conceptualization of the waqf program crowdfunding system implemented by an online donation platform and strategies for increasing waqf digitization. This research uses a descriptive qualitative method by collecting data through in-depth interviews with application managers, waqf institutions’ leaders, donors, and documentation. The results of this study show that the crowdfunding system runs through the stages of the waqf program proposal, verification of publications and socialization of the waqf program. The donation platform’s strategy in increasing the digitization of waqf includes providing access to waqf institutions for program approvals, notification of sustainable programs, additional features of Islamic studies on the application, digital publications of creative waqf programs, surveys of digital waqf program locations, creation of digital content and videos of waqf activities. In addition, other strategies include solicitations and response and input spaces on the application. The crowdfunding system implemented by the Amalsholeh platform can help waqf institutions find donors and increase community interest in online waqf or digitalization of waqf. Keywords: crowdfunding system, waqf, waqf digitization strategy.